Synergetic effect of natural ageing and pre-stretching on the ageing behavior in Tʹ/ηʹ phase-strengthened Al-Zn-Mg-Cu alloys. (20th May 2023) - Zou, Yan; Cao, Lingfei; Wu, Xiaodong; Tang, Songbai; Guo, Mingxing
Highlights: The effect of a novel combinatorial pre-treatment on the hardening behavior and microstructure evolution was investigated. GP I zones formed during natural ageing are helpful to the uniform distribution of dislocations introduced by pre-stretching. The synergetic effect of combinatorial pre-treatment was compared in T'/η' phase-strengthened Al-Zn-Mg-Cu alloys. The peak hardness of combinatorial pre-treated alloys was unaffected by the pre-stretching strain. Abstract: Al-Zn-Mg-Cu alloys with different major strengthening precipitates are subjected to a novel combinatorial pre-treatment, including natural ageing and pre-stretching. The evolution of hardness and microstructure during the combinatorial pre-treatment and subsequent artificial ageing has been investigated. The results reveal that the growth rate of hardness in alloy B (Zn/Mg = 10.0) is much higher than that of alloy A (Zn/Mg = 1.5) due to the fast precipitation kinetics of η′ phase compared with T′ phase. Both GP I zones and dislocations introduced by the combinatorial pre-treatment can act as heterogeneous nucleation sites for precipitation, resulting in more precipitates and higher hardness than pre-stretched alloys A and B. Dislocations distribute uniformly in combinatorial pre-treated alloys owing to the existence of GP I zones and dislocations, which promote the precipitation and refine the precipitate size. Moreover, these alloys with distinct pre-stretching (2%–10%) show similar precipitation behavior and peak hardness, and it indicates that the dislocation-induced precipitation will not be affected by the density of dislocations when plenty of GP I zones pre-exist.